Marsward and tailward ions in the near‐Mars magnetotail: MAVEN observations. Issue 21 (5th November 2015) - Harada, Y.; Halekas, J. S.; McFadden, J. P.; Mitchell, D. L.; Mazelle, C.; Connerney, J. E. P.; Espley, J.; Larson, D. E.; Brain, D. A.; DiBraccio, G. A.; Curry, S. M.; Hara, T.; et al.
Abstract: We present Mars Atmosphere and Volatile EvolutioN (MAVEN) observations of Marsward and tailward fluxes of suprathermal (>25 eV) ions in the near‐Mars (∼1–1.5 Mars radii downstream) magnetotail. Statistical results show that the Marsward proton flux and magnetic field draping pattern are well organized by the upstream motional electric field direction. We observe both significant Marsward proton fluxes and tightly wrapped magnetic field lines in the hemisphere pointed in the opposite direction to the upstream electric field. These characteristics are very similar to those observed at Venus. On the other hand, the net flux of oxygen ions points tailward on average in the Martian tail, while net Venusward flows of oxygen ions were observed frequently in the same hemisphere at Venus. The mechanism by which the Marsward proton flux is produced in the presence of tailward oxygen ion flux remains unclear. Key Points: Ions and magnetic fields in the near‐Mars tail are organized by the upstream electric field Marsward protons and wrapped field lines are observed in the − E hemisphere Unlike at Venus, net flux directions differ between protons and oxygen ions at Mars